Wayne Doehring with glass polymerizer in Glass Fabrication department - Dow Chemical Company (1957)
General view of Wayne Doehring placing a glass polymerizer into the annealing furnace in the Dow Chemical Company's Glass Fabrication department. Founded in 1925, the department was responsible for the fabrication and repair of specialty glass equipment used at the Company's plant in Midland, Michigan. Before leaving the department, glass was placed in the furnace to remove any stresses that set up in the glass during fabrication.
Keywords: Employees; Laboratories; Dow Chemical Company; Glass manufacture; Furnaces; Glassware; Doehring, Wayne